Machine translation use outside the language industries: a comparison of five delivery formats for machine translation literacy instruction - Bowker, Lynne (Université d'Ottawa | University of Ottawa, 2021)
Since the release of the first free online machine translation systems around 15 years ago, machine translation (MT) has been “in the wild”, meaning it is available to users outside the language industries. However, most user-related investigations of MT focus on how this technology is used by language professionals, such as translators. As the user base outside the language professions grows, it is worth understanding more about who is using MT and why as this could help to inform future developments of the tools. Based on my experience of teaching MT to non-translation students in five different university-level contexts in the 2020/2021 academic year, I share some insights about who these users are, why they are using MT, and how satisfied they are with the results.
Keywords: machine translation; machine translation literacy; translation pedagogy